Analisis Strategi Pengembangan UMKM dalam Meningkatkan Pendapatan Masyarakat Desa Padang Brahrang Kec.Selesai Kab.Langkat (Studi Kasus Pada Home Industri Krupuk & Keripik) - Suci Rahmadani (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
Home Industry is a productive economic business opportunity carried out by individuals or business entities in order to increase income. Home Industry or UMKM consisting of local people who are looking for additional income to meet their daily needs, because the products produced are processed snack products at affordable prices. Based on the observations made, it shows that this home industry uses a marketing mix development strategy which includes halal products, affordable prices, and transparent promotions, so it can be concluded that the UMKM (home industry) snacks belonging to Mr. Sandi and Mrs. Riska who are in the village of Padang Brahrang, District of Selesai, Regency of Langkat, experiencing developments that continue to improve from the increasing number of consumers/markets as well as people's incomes getting better. This home industry has an important role, namely opening up jobs for the local community in increasing income so that it can meet the needs of their families such as the fulfillment of food, health, shelter, educational needs for their children and other needs.